Transcytosis in the development and morphogenesis of epithelial tissues - Serra, Nicholas D (EMBO J, 2021)
Transcytosis is a form of specialized transport through which an extracellular cargo is endocytosed, shuttled across the cytoplasm in membrane‐bound vesicles, and secreted at a different plasma membrane surface. This important process allows membrane‐impermeable macromolecules to pass through a cell and become accessible to adjacent cells and tissue compartments. Transcytosis also promotes redistribution of plasma membrane proteins and lipids to different regions of the cell surface. Here we review transcytosis and highlight in vivo studies showing how developing epithelial cells use it to change shape, to migrate, and to relocalize signaling molecules.